A clinical study of the benefits and effectiveness of a respiratory viral panel PCR study in children presenting with respiratory tract infections. (2nd April 2022) - Thattakkat, Krishnakumar
Abstract : Introduction: Respiratory illnesses account for more than half of paediatric diseases and it is often difficult to differentiate viral and bacterial agents by clinical assessment, leading to unnecessary investigations and interventions including hospitalisation and use of antibiotics. A respiratory virus panel (RVP) multiplex polymerase chain reaction (PCR) test can identify the pathogen rapidly with specificity. The objective of this study was to explore the characteristics and outcomes of children who had RVP PCR and to identify its impact on the use of antibiotics, hospitalisation, and revisit and readmission rates. Methods: The medical records of 100 children under 18 years old in one hospital in Dubai who had an RVP PCR test in December 2019 were reviewed to investigate the type of pathogen identified as well as hospitalisation and antibiotic use rates. Results: Out of 100 children, 85 had a positive RVP result. Rhino/enterovirus was the single most common virus (28.8%) identified. There was a hospital admission rate of 9%, as one baby in the neonatal intensive care unit had an RVP PCR test during the study period. This baby was excluded during the statistical analysis as the baby was not an outpatient at the time of testing. Seven children received antibiotics. Of the 87 patients sent home, 10 (11.5%) only received antibiotics. Overall, 14 patients revisited the hospital within 1 week. There was no antibiotic use at follow up and the readmission rate was 0%. Conclusions: This study illustrates that a positive RVP PCR result leads to beneficial outcomes such as low rates of hospitalisation and antibiotic use. With thoughtful clinical correlation, the RVP PCR can be a useful and cost-effective tool for clinical management.